Pembelajaran Daring Dengan Keterbatasan Akses Internet di Pelosok Desa Era Covid-19 (Studi Kasus SMK Telkom Medan) - Jamaludin Jamaludin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
This study aims to find out the problems experienced by some students, especially those who live in remote villages related to limited internet network access during the Covid-19 pandemic. This research uses the activity method with continuing education. The subjects sampled in the study were four students of SMK Telkom Medan who live in four different villages with different conditions of limited internet network access. Based on the findings of the researchers, even though they face obstacles in online learning, they are still enthusiastic and struggle to be able to continue online learning despite their limitations. This is very different for students who live in cities with complete facilities but their learning motivation is very low. Then the online activities of some students who had online problems in remote villages were documented and made videos which were then published through social media and online media so that they hoped to generate learning motivation for other students who live with adequate facilities and infrastructure.